Positive Body Image and Identity Formation among Senior Secondary School Adolescents in Ibadan South-East Local Government Area, Oyo State - Sabina Nwakaego Obi (INSIGHT: Jurnal Bimbingan Konseling, 2025)
Adolescence is a critical developmental stage characterised by rapid physical, psychological, and social changes. For Nigerian adolescents, this period is further complicated by the interplay of cultural expectations, peer influence, and globalised media, which often impose conflicting ideals of appearance and identity. This study investigated the relationship between positive body image and identity formation among senior secondary school adolescents in Ibadan South-East Local Government Area, Oyo State. A correlational research design was employed, with a sample of 200 students drawn randomly from four public schools. Data were collected using the Positive Body Image among Adolescents Scale (PBIAS) and the Functions of Identity Scale (FIS). Descriptive statistics summarised adolescents’ responses, while Pearson’s Product-Moment Correlation tested the hypothesis at the 0.05 significance level. Findings revealed a generally high level of positive body image, with the strongest endorsements for self-acceptance and body respect, although coping with media-driven body ideals was weaker. Identity formation was reported at a very high level, with adolescents showing strong self-acceptance, value alignment, and parental influence, though many expressed uncertainty about future direction and life goals. The correlation results showed a significant moderate-to-strong positive relationship between positive body image and identity formation (r = .597, p < .01), leading to the rejection of the null hypothesis. The study concludes that positive body image enhances adolescents’ ability to build coherent identities, while cultural and media influences interact to shape outcomes.